EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

Check GES Ghana Learning TV (GLTV) Timetable For JHS, Primary, KG: How To Scan For GLTV - Avenuegh Online Portal (2020)
The Ghana Education Service (GES) has officially released the Ghana Learning TV (GLTV) timetable for

Minister for Education, US Ambassador launch Ghana Learning Radio Reading Program - Ghana Ministry of Education (Ghana Ministry of Education, 2020)
The Minister for Education, Dr. Matthew Opoku Prempeh, together with the   U.S. Ambassador to Ghana Stephanie S. Sullivan has launched the Ghana Learning Radio reading program. The radio program, which was developed in response to the closure of basic schools across the country due to the COVID-19 global pandemic, aims to engage parents, guardians/ caregivers, […]

Ghana: Mobile Phone and Digital Devices in the Classroom - Learning Tool or Distraction - Darkwa, O.K. (2020)
Globally, mobile technology use has increased over the years and the use of it has become an integral part in the average persons' communicative lifestyle. According to Parsons, mobile subscriptions exceed 6 billion subscriptions globally. Similarly, Ipsos and Verizon found out that adopting mobile phones with smart technologies has increased fast which also coincided with a more utilization of their Internet capabilities. People today are more connected than ever.

EDUCATION REFORM - Ministry of Education Ghana - Ministry of Education Ghana (2020)
The Ghana Education Reform Agenda The Government of Ghana initiated some key education reforms to transform teaching and learning and improve educational outcomes under the Education Strategic Plan (ESP 2018-2030) which was approved by cabinet in November 2018. These reforms are expected to contribute to the goals of the ESP and the Sustainable Development Goals

COVID-19 Coordinated Education Response Plan for Ghana - Ministry of Education, Ghana (2020)

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

COVID-19 Coordinated Education Response Plan for Ghana - Ghana Education Services (2020)

Teachers’ digital literacy and digital activity as digital divide components among basic schools in Ghana - Quaicoe, James Sunney; Pata, Kai (Education and Information Technologies, 2020)
This survey-based study explores the nature of Digital Divide among Ghana’s basic (primary and junior high) schools from the perspective of Teachers’ Digital Literacy and their usage of digital technologies in school. The ICT-enhanced Teacher Standards for Africa (ICTeTSA) Framework comprising digital attitude, knowledge, skills and application components was used for measuring the perceived Teacher Digital Literacy, while, the European Union’s rubrics for measuring ICT frequency in schools was adopted for estimating the extent of teachers’ digital technology usage/activities. The study covered six districts in Ghana with 233 teachers (n = 233) sampled from 45 schools. Based perceptions of the Teacher Digital Literacy two significantly different Digital Divide clusters were found among schools that diverged based on the teachers’ digital application component of Teacher Digital Literacy. While, most schools teachers claimed an above average level of Teacher Digital Literacy; however, more than 50% of the schools are digitally proactive. Suggesting that teachers appear not to be actually using ICT tools and digital resources for professional practice. The cluster of schools differentiated by the extent of digital activities (TDA) were performed weekly. The study reveals several critical issues of teachers’ digital empowerment for technology in Ghana’s basic schools, of which school-based management (SBM) governance be adapted to address them.

Primary and Secondary Impacts of the COVID-19 Pandemic on Children and Women in Ghana - UNICEF (COVID-19 IMPacts on Children, 2020)

Ghana Learning TV May Timetable from KG to SHS - Ghana Education Service (2020)

External Validity: Four Models of Improving Student Achievement - Duflo, Annie; Kiessel, Jessica; Lucas, Adrienne (National Bureau of Economic Research, 2020)
Randomized controlled trials in lower-income countries have demonstrated ways to increase learning, in speciﬁc settings. This study uses a large-scale, nationwide RCT in Ghana to show the external validity of four school-based interventions inspired by other RCTs. Even though the government implemented the programs within existing systems, student learning increased across all four models, more so for female than male students, and many gains persisted one year after the program ended. Three of the four interventions had a similar cost eﬀectiveness. The intervention that directly targeted classroom teachers increased the likelihood that teachers were engaged with students.
Keywords: C:Ghana

Ghana - Demographic Dividend (2020)

What COVID-19 reveals about educational inequality in Ghana - Mohammed, W.F. (2020)

Early Grade Reading Evaluation in Ghana: Unprecedented Results and Policy Impacts - Social Impact (2020)

Trapped in low performance? Tracking the learning trajectory of disadvantaged girls and boys in the Complementary Basic Education programme in Ghana | Elsevier Enhanced Reader - McCulloch, Gretchen (2020)

Demographic Dividend Country Highlights - Ghana - Demographic Dividend (Demographic Dividend, 2020)

USAID Partnership for Education - USAID (Global Reading Network, 2020)
The USAID Ghana Partnership for Education: Learning activity developed a phonics-based reading program that will provide evidence-based tools and strategies for improving reading performance in 100 districts in Ghana, reaching approximately 1.1 million primary students. This brochure provides an overview of Learning’s approach, which includes teacher professional development models, methods for scaling up, a model for primary mathematics, a rigorous monitoring and support system and a learning-by-doing approach to capacity development. The brochure also highlights strong results from a prototype of the program conducted in the Dagbani language.

Education Ministry creates special online study platform for SHS students (2020)
The Ministry for Education has launched a special online study platform for Senior High School students. Ever since Covid-19 halted school activities the Education Ministry together with the Ghana Education Service has stepped up efforts to help...

RECOVR Ghana: Tracking the Effects of the COVID-19 Pandemic. Innovations for Poverty Action. - Innovations for Poverty Action (Poverty Action, 2020)

Towards e-learning in basic schools during Covid-19: Insights from Ghanaian teachers - Amanor-Mfoafo, Naa Kai; Edonu, Kwamina Kurefi; Akrofi, Olivia; Dowuona, Ebenezer Nortei (2020)
In the wake of the current closure of schools in Ghana, basic schools have been tasked to deliver teaching and learning using e-learning. This study seeks to explore the readiness of teachers in Ghanaian basic schools to undertake e-learning. Using an online questionnaire, data was collected from 108 teachers in both private and public basic schools in Ghana. A factor analysis was conducted to identify the challenges that influenced the ability of basic school teachers to teach using e-learning. The study findings indicated that a majority of the teacher participants preferred face-to-face teaching as compared to online teaching. The study recommends that basic schools adopt a blended approach to teaching where teachers can combine both face-to-face methods with e-learning methods. The study contributes to discussions on the transition from conventional teaching methods to E-learning methods in educational institutions across Ghana.

2020 Formula for sharing the DACF. 2020 - Parliament of Ghana (Government of the Republic of Ghana, 2020)

Mezzanine (Vodacom Ghana, 2020)

“I’m not against online teaching, but what about us?”: ICT in Ghana post Covid-19 - Adarkwah, Michael Agyemang (Education and Information Technologies, 2020)
Globally, Information and Communication Technology (ICT) is regarded as a dependable vehicle for facilitating educational reform and development, a platform for communication, and as a means to achieve the Sustainable Development Goal Four (SDG 4). Since the enactment of the No Child Left Behind Act (NCLB) and declaration of the SDG 4, many countries have opted to embrace the lifelong education for all by integrating ICT in teaching and learning at all school levels. The Ghanaian Government’s initiative to ensure “education anytime anywhere for everyone” by revolutionizing teaching and learning through ICT has faced a lot of challenges and criticisms. The main mission of the Ghana ICT for Accelerated Development (ICT4AD) in 2003 was to transform Ghana into an information and technology-driven high-income economy through education, but this goal is yet to be realized. In the wake of the COVID-19 which has forced many countries and educational sectors to adopt online learning, there is a need to discuss the effectiveness of online learning and barriers to online learning in the developing contexts, and how to successfully integrate ICT in schools for online learning, especially rural schools where students’ educational careers are in jeopardy because they benefit less from online learning. The paper identifies critical factors that affect online learning, recommends post COVID-19 strategies to promote e-learning for policymakers in education and the government, and concludes with a conceptual model for emergency transition to e-learning.

Tertiary students’ engagement with professional learning networks and emerging technologies in learning: The case of a coastal University in West Africa. - Wiafe, Bernard; Takramah, Florence; Bless, Gloria; Akaadom, Bernard (International Multidisciplinary Research Journal, 2020)
The main aim of this study was to investigate students' views on their engagement with professional learning networks and emerging technologies for students' use and how these impact their studies. A sample of 150 students from the University of Cape Coast, Ghana was used for study. Respondents were selected from second year to final year students pursuing undergraduate degree programmes from three different departments of the university. The research instrument used was a carefully constructed questionnaire. Undergraduate students generally exhibited positive attitude towards the use of professional learning networks and emerging technologies across the five attitudinal subscales they were measured on. As a result, from the findings, it is recommended that the use of professional learning networks and emerging technologies should be taken advantage of at all levels in a university curriculum.
Keywords: ⛔ No DOI found

Improving the Mouse Skills of Basic School Learners Using the Optical Mouse and Self Instructional Software. A Case of a Ghanaian Basic School - Asare, Samuel; Leticia, Agyemang (Innovation The European Journal of Social Science Research, 2020)
The study came about as a result of poor performance showed by Bosofour R\C primary 6 learners' during practical sessions. The general objective of the study is to examine the causes of learner's poor mouse skills and provide an immediate solution to it. The research was conducted at Bosofour R\C primary school from the month of December, 2019 to June, 2020. The study was critically analyzed, though ICT is a core subject offered by all learners' in the school, but due to time constraint, nature of the research and inadequate financial support, all the classes could not be covered but few were sampled to represent the whole school. The study adopted a random sampling technique for its appropriateness in reaching out to a large representative sample and generalization of the findings. The target population included five hundred and twenty (520) learners, comprising of two hundred and forty-eight (248) boys and two hundred and seventy-two (272) girls. Random sampling techniques was used to select twenty (20) learners'. Test, interview and observation were the main instruments used for data collection. The main design for the study was action research. The collected data was analyzed with the help of frequency distribution table, using pre-test and post-test as a method of obtaining data. The challenges of the study include; insufficient time for practical activity lessons, abstract methods of teaching, inadequate teaching\ learning resources and teachers' pedagogical knowledge about the course. The results of the study showed that learners' mouse skills may be improved by the use of optical mouse, self-instructional software and giving students enough time during practical sessions. It is therefore recommended that, Ghana Education Service should equip all Basic schools across the country with several types of educational software's, in addition in-service training on ICT should be provided for all teachers, and finally, much time should be allotted for ICT practical activity lessons.
Keywords: ⛔ No DOI found

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Ghana Accountability for Learning Outcomes Project - World Bank (2020)

Ghana COVID-19 Accelerated Funding Application Form - Global Partnership for Education (2020)

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

2020 EdTech Ecosystem: Ghana and Cote D'ivoire - Jacobs Foundation (Jacobs Foundation and Chrysalis, 2020)

Report: The Impact of COVID-19 Across Africa - Elliott, Roxana (GeoPoll, 2020)
New report on coronavirus in sub-Saharan Africa including data from Kenya, Ghana, South Africa, Nigeria. COVID-19 and food security, economic impact.

Do civil service performance incentives work: Evidence from Ghana and Zambia - Williams, Martin (International Growth Centre, 2020)

Online learning in higher education during COVID-19 pandemic: A case of ghana - AGORMEDAH, Edmond Kwesi; HENAKU, Eugene ADU; AYİTE, Desire Mawuko Komla; ANSAH, Enoch APORİ (Journal of Educational Technology and Online Learning, 2020)
Keywords: ⛔ No DOI found

COVID-19 and e-learning: the challenges of students in tertiary institutions in Ghana - Aboagye, Emmanuel; Yawson, Joseph Anthony; Appiah, Kofi Nyantakyi (Social Education Research, 2020)
Problems associated with the transition from conventional learning (face to face) to online learning (e-learning) in the educational system are well documented. The present study explores the challenges students in tertiary institutions have reported facing in online learning in the era of coronavirus pandemic. Using a sample (n = 141), an initial principal component factor analysis was conducted to group the constructs. Eight groups that emerged were social issues, lecturer issues, accessibility issues, learner motivation, academic issues, generic issues, learner intentions, and demographics. Cronbach’s alpha was used to determine the reliability of the scales resulting in the deletion of learner motivation. Comparing the means of the factors revealed that the most important challenge for students to study online was accessibility issues. This was followed by social issues, lecturer issues, academic issues, and generic issues. The mean for the individual items in learners’ intention to study online showed that students were not ready to study online. A Multiple Regression Analysis was further conducted to determine which factors pose the most important challenges to the student’s decision to study online. Social issues and lecturer issues were significant. In the final model, only lecturer issues were significant. A blended approach-where conventional teaching is combined with online teaching should have ushered the learners to complete online learning.

Launching sign languages on the Global Digital Library - Global Digital Library (Global Digital Library, 2020)

Sustaining literacy from mother tongue instruction in complementary education into official language of instruction in government schools in Ghana - Carter, Emma; Sabates, Ricardo; Rose, Pauline; Akyeampong, Kwame (International Journal of Educational Development, 2020)

Universities to reopen in mid-June to final-year students - Kokutse, F. (2020)

MIT Solve (2020)

Instant Network Schools (Vodafone, 2020)

Local Content for African Libraries (Worldreader, 2020)
The LOCAL project aims to bring local books to libraries and ensure that children can learn in their mother-tongue language.

Mobile School Report Card (mSRC, 2020)

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Open educational resources - EdTech Hub (EdTech Hub, 2020)
As part of our COVID-19 response, the EdTech Hub is collecting and facilitating access to open educational resources (OER). Open educational resources are teaching, learning and research materials that are made freely available for anyone to access and re-use. These documents are currently stored on Google Drive (no sign-in required). We will add additional distribution […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Covid-19 Crisis: UNESCO Call to Support Learning and Knowledge Sharing through Open Educational Resources - UNESCO (UNESCO, 2020)
In response to the massive disruption of education due to the Covid-19 pandemic affecting 1.57 billion learners in 191 countries, UNESCO has issued a Call to support learning and knowledge sharing through Open Educational Resources (OER) worldwide. OER are learning, teaching and research materials in any format and medium that reside in the public domain or are under copyright released under an open license[1], permitting no-cost access, re-use, re-purpose, adaptation and redistribution by others.

Language counts when learning mathematics with interactive apps - Outhwaite, Laura A.; Gulliford, Anthea; Pitchford, Nicola J. (British Journal of Educational Technology, 2020)
When available in multiple languages, educational apps can deliver the same mathematics instruction in the child’s first language or different language of instruction. This pilot study examined the ...

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Learning through television in low-income contexts: mitigating the impact of coronavirus (COVID-19) - Watson, Joe (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Joe Watson, research assistant at the University of Cambridge One of the many consequences of COVID-19 is that more than a billion caregivers will soon face the stark (and often scary) realisation that they must become their children’s teachers. This will be particularly difficult in low-income contexts where…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

THE IMPACT OF COVID-19 ON LEARNING - THE PERSPECTIVE OF THE GHANAIAN STUDENT - Owusu-Fordjour, C.; Koomson, C. K.; Hanson, D. (European Journal of Education Studies, 2020)
This study aimed at accessing the impact of Covid-19 on Ghana’s teaching and learning. The study employed a Descriptive survey design in which 11 items Likert-scale type of questionnaires was administered to 214 respondents mainly students in the second cycle and tertiary institutions of Ghana. The study employed simple random sampling technique in selecting the respondents for the study. The study revealed some challenges students encounter in the close down of schools due to the outbreak of the pandemic Covid-19: Students are unable to study effectively from the house thus, making the online system of learning very ineffective. Again, parents are incapable of assisting their wards on how to access online learning platform, neither can they entirely supervise the learning of their children at home without any complications. It came to light that the pandemic really has had a negative impact on their learning as many of them are not used to effectively learn by themselves. The e-learning platforms rolled out also poses challenge to majority of the students because of the limited access to internet and lack of the technical knowhow of these technological devices by most Ghanaian students. The study therefore recommends that students should be introduced to e-learning platforms to supplement classroom teaching and learning.  Article visualizations:
Keywords: emotions; highlife music; lyrics; popular music; structure; ⚠️ Invalid DOI

Eneza Education website - Eneza Education (Eneza Education, 2020)
Eneza Education is an ed-tech company that provides curriculum aligned revision material in all subjects for primary and secondary learners on any device. Our virtual tutor provides access to curriculum-aligned ... Read More

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Educational Technology in Developing Countries: A Systematic Review - Rodriguez-Segura, Daniel (EdPolicyWorks Working Paper, 2020)
Keywords: ___working_potential_duplicate

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Conseils pour l’introduction de la technologie en classe Liste de sources annotée - Allier-Gagneur, Zoé; Lwamba, Etienne (EdTech Hub, 2020)
Cette liste de sources annotée a pour but d’informer la prise de décisions des acteurs du domaine de l’éducation concernant l’introduction de technologies en classe dans les pays à revenu faible et intermédiaire. Cette liste est une introduction qui expose de façon informelle certains des conseils généraux que prodiguent souvent les experts de l’EdTech Hub.
Keywords: F: Helpdesk response; LP: French; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Child-directed Tablet-based Learning: Project Launch, Monitoring, and Improvement Toolkit - Imagine Worldwide (2020)

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode